FROM SURFACE TO DEEP: FOSTERING DEEP LEARNING COMPETENCIES (6CS) THROUGH CULTURALLY-GROUNDED STEM BIG BOOKS IN INDONESIAN EARLY CHILDHOOD EDUCATION - Titi Chandrawati; Sri Tatminingsih; Dian Novita; Uliya Khoirun Nisa; Monika Handayani; Susy Puspitasari; Andayani (COMPASS: Journal of Education and Counselling, 2026)
Early childhood STEM education often remains focused on surface learning, limiting children’s ability to transfer knowledge into meaningful behavior and long-term understanding. This study aimed to investigate how culturally grounded STEM Big Books foster deep learning competencies among children aged 4–6 years in Indonesian early childhood education settings. The study employed a Research and Development design involving 32 teachers and approximately 150 children across several ECE institutions in Indonesia, using pre-post assessment, teacher evaluation, classroom observation, and qualitative reflection data. The findings demonstrated significant improvements across multiple dimensions of the 6Cs framework, particularly character, citizenship, collaboration, communication, and critical thinking. Children showed stronger conceptual understanding, spontaneous environmental behavior, collaborative problem-solving, and transfer of learning into home contexts. The study also identified four key mechanisms supporting deep learning: cultural anchoring, narrative embedding, multimodal exposure, and social co-construction. These findings suggest that culturally responsive STEM pedagogy can support transformative learning experiences in early childhood education.